Diseño de un sistema de dosificación de agregados para la Compañia de Ingenieria y Mantenimiento CIM SAS (2019)
In this project the “Design of a raw material dosage system for the engineering and maintenance company CIM S.A.S” was carried out with the purpose of implementing production planning and programming strategies that will lead to increased productivity. Once one of the three alternatives on the sand dosing subsystem was selected, the specific details of the design were calculated, the materials and dimensions were selected according to the efforts made on the piece, an analysis of the structure was carried out by By means of the finite element method, the necessary plans for the development of the system were developed, the operation, maintenance and installation manuals were prepared, with their respective recommendations. Finally, the financial viability of the project and the environmental impact were evaluated.